Thermal performance evaluation of a channel with twisted baffles installed: Effect of twisted baffle arrangement - Eiamsa-ard, S.; Pingta, S.; Phila, A.; Woncharee, K.; Chamoli, S.; Thianpong, C. (My University, 2026)
This research aims to introduce newly designed twisted baffle for enhancing heat transfer in solar air heater. This study examined the thermo-hydraulic performance of converging twisted baffles (C-TBs) and diverging twisted baffles (D-TBs) with different numbers of loops (n = 2, 4, 6, and 8) over a Reynolds number range (Re) of 6000–24,000. The results demonstrated that both converging twisted baffles and diverging twisted baffles significantly enhanced heat transfer compared to a smooth channel. The Nusselt number, friction factor, and thermal performance factor (TPF) increased as the number of loops decreased, attributed to stronger flow reattachment. Specifically, twisted baffles with 2, 4, 6, and 8 loops enhanced Nu by approximately 2.29–3.43, 2.02–3.05, 1.77–2.74, and 1.61–2.48 times, respectively, while the friction factor increased by 5.19–5.71, 4.61–5.01, 4.06–4.43, and 3.73–4.06 times, respectively. For a given number of loops, diverging twisted baffles consistently provided higher heat transfer enhancement than converging twisted baffles, albeit with slightly increased friction losses. Across the investigated range, the 2-loop diverging twisted baffles exhibited the best overall performance, achieving the highest Nusselt number ratio (Nu/NuSC where NuSC is the Nusselt number of the smooth channel) of 3.43 and a maximum thermal performance factor of 1.92 at Reynolds number of 6000, establishing it as the optimal configuration among those tested. This research contributes valuable design guidelines for selecting optimal baffle configurations, thereby supporting the development of more energy-efficient solar thermal systems.
Keywords: Heat exchanger; Heat transfer enhancement; Solar air heater; Thermal performance; Twisted baffle